Relation of Pleurocapsa cuprea Hansgirg to the genus Hildenbrandia (Rhodophyta) - Caisová, Lenka (Jihočeská univerzita, 2011)
Pleurocapsa cuprea has been originally described as a relatively common freshwater cyanobacteial species with specific habitat preferences. Due to the striking resemblance of some diagnostic features to the red algal genus Hildenbrandia, morphological, molecular as well as pigment analyses have been done to either confirm or disprove the relationship of Pleurocapsa cuprea to the Cyanobacteria.
Relation of Pleurocapsa cuprea Hansgirg to the genus Hildenbrandia (Rhodophyta)